Characteristics of the Reacting Flow for the Base‐Bleed Projectile under Dual Stress. Issue 12 (28th October 2021) - Zhou, Shupei; Yu, Yonggang; Ye, Zhenwei; Ma, Longze
Abstract: While the base‐bleed projectile (BBP) is ejected from the muzzle, high‐speed rotation and rapid depressurization in the combustion chamber bring much initial disturbance to the BBP. In order to research the effect of propellant gas on the drag reduction performance for the BBP, a chemical non‐equilibrium flow model is established under the dual environmental stress of high‐speed rotation and rapid depressurization. This numerical model is coupled with a H2 ‐CO reaction mechanism and propellant burning rate model. Detailed numerical results of flow patterns, heat energy addition, and mass addition for various rotation speeds are discussed. The results show that the supersonic under‐expanded jet gradually transforms into a subsonic jet, and a low‐pressure recirculation zone appears at the wake of BBP. Moreover, the tangential velocity in the combustion chamber presents a typical distribution of the Rankie combined vortex. The high‐pressure jet rapidly expands to the outside low‐pressure environment, and the pressure in the combustion chamber ( p c ) drops sharply. After 1.15 ms, the outside gas flows back into the combustion chamber, and the rotation increases the fluctuation intensity of the inter flow field. p c reaches 0.718  p 0 and remains stable after 4.0 ms. The rotation of BBP increases the pressure and Mach number near the nozzle at 5.0 ms. Abstract :